An Unusual First Manifestation of Hodgkin Lymphoma: Epitrochlear Lymph Node İnvolvement-A Case Report and Brief Review of Literature - Veysi Hakan Yardimci MD; Aytul Hande Yardimci MD (SAGE Publishing, 2017)
Although epitrochlear lymph nodes may be enlarged as a part of generalized lymphadenopathy, isolated enlargement of epitrochlear lymph nodes is rarely seen. We describe Hodgkin's lymphoma in a 55-year-old male who presented with isolated epitrochlear lymphadenopathy of his right arm. In the histopathological examination of the epitrochlear lymph node was a lymphocyte-rich Hodgkin lymphoma with a clinical grade (CS IA) diagnosed. The diagnosis was confirmed, via the bone marrow biopsy and positron emission tomography/computed tomography imaging, as pathological stage PS IA and clinical stage CS IA. Epitrochlear lymph node involvement, as a first presentation, is rarely seen in Hodgkin's lymphoma. The aim of this study was to recapitulate the possible background diseases arising on the basis of an asymptomatic epitrochlear lymphadenopathy, to review the Hodgkin lymphoma presenting with primary epitrochlear lymphadenopathy in light of the literature, and to highlight the importance of a careful examination of the elbow site in routine physical examination.